Burkholderia multivorans: A rare yet emerging cause of bacterial meningitis. (2018) - Peralta, Diego P.; Chang, Aymara Y.; Ariza-Hutchinson, Angie; Ho, Catherine A.
Abstract: Burkholderia multivorans is a member of the Burkholderia cepacia complex. Although it is usually associated with infections in patients with cystic fibrosis, chronic granulomatous disease, and immunosuppression, central nervous infections are not commonly reported. Moreover, management of these infections is difficult due to multiple mechanisms of bacterial resistance to antimicrobial agents. We report a 55-year-old-man who developed Burkholderia multivorans meningitis after two episodes of central line-associated bloodstream infections. The patient was successfully treated with intravenous trimethoprim/sulfamethoxazole. Burkholderia multivorans is an emerging cause of meningitis with limited antibacterial treatment options. However, trimethoprim/sulfamethoxazole remains an effective agent with excellent penetration into the central nervous system. To our knowledge, this is the first case reported of Burkholderia cepacia complex meningitis identified to the species level as Burkholderia multivorans.